An Introductory Framework for Choosing Spatiotemporal Analytical Tools in Population-Level Eco-Epidemiological Research - Kanankege, Kaushi S. T.; Alvarez, Julio; Zhang, Lin; Perez, Andres M. (Frontiers in Veterinary Science, 2020)
Spatiotemporal visualization and analytical tools (SATs) are increasingly being applied to risk-based surveillance/monitoring of adverse health events affecting humans, animals, and ecosystems. Different disciplines use diverse SATs to address similar research questions. The juxtaposition of these diverse techniques provides a list of options for researchers who are new to population-level spatial eco-epidemiology. Here, we are conducting a narrative review to provide an overview of the multiple available SATs, and introducing a framework for choosing among them when addressing common research questions across disciplines. The framework is comprised of three stages: a) pre-hypothesis testing stage, in which hypotheses regarding the spatial dependence of events are generated; b) primary hypothesis testing stage, in which the existence of spatial dependence and patterns are tested; and c) secondary-hypothesis testing and spatial modeling stage, in which predictions and inferences were made based on the identified spatial dependences and associated covariates. In this step-wise process, six key research questions are formulated, and the answers to those questions should lead researchers to select one or more methods from four broad categories of SATs: T1) visualization and descriptive analysis; T2) spatial/spatiotemporal dependence and pattern recognition; T3) spatial smoothing and interpolation; and T4) geographic correlation studies (i.e. spatial modeling and regression). The SATs described here include both those used for decades and also other relatively new tools. Through this framework review, we intend to facilitate the choice among available SATs and promote their interdisciplinary use to support improving human, animal, and ecosystem health.